An efficient way to synthesize biomass-based molybdenum carbide catalyst via pyrolysis carbonization and its application for lignin catalytic pyrolysis. (February 2022) - Yu, Jiajun; Luo, Bingbing; Wang, Yihan; Wang, Siyu; Wu, Kai; Liu, Chao; Chu, Sheng; Zhang, Huiyan
Graphical abstract: Highlights: Efficient preparation of orthorhombic α-Mo2 C for lignin catalytic pyrolysis. In situ pyrolysis products of biomass can promote the carbonization of MoO2 . The yield of MAHs after pyrolysis and catalytic conversion of lignin was 13.26%. Aromatic hydrocarbon products are rich in side chain aliphatic hydrocarbons. Pine-Mo2 C catalyst shows excellent direct deoxidation performance. Abstract: In this study, a simple and rapid method was proposed to synthesize orthorhombic α-Mo2 C as catalyst for lignin catalytic pyrolysis. Biomass in-situ pyrolysis products were used as the carbon source and supporter, the carbonization of Mo precursor was realized under rapid heating. Experimental results show that Pine-Mo2 C catalyst can achieve lignin pyrolysis vapor bond breaking and deoxidation under normal pressure, and the yield of monocyclic aromatic hydrocarbons is 13.26 wt%, of which aromatic hydrocarbons with side chain account for 74%. The side chain aliphatic hydrocarbons of lignin are effectively retained, and hydrogen consumption is minimized. The characterization of catalyst and experiments of guaiacol, 2-phenoxy-1-phenylethanol and 4, 4′-biphenol shows that efficient deoxidation is due to targeted attack of catalyst on C-O. Therefore, Pine-Mo2 C shows excellent activity in promoting direct bond breaking deoxidation of lignin.